Infancia y represión: historias para no olvidar; experiencia clínica con niños y familias que han vivido la represión política - Alamos Varas, Loreto (Fundación PIDEE, 1992)
"Detailed case histories and an evaluation of the impact of different therapeutical approaches make this work a valuable resource on families and children victimized by political repression"--Handbook of Latin American Studies, v. 57